Direct monitoring of light mediated hyperthermia induced within mammalian tissues using surface enhanced spatially offset Raman spectroscopy (T-SESORS). Issue 11 (3rd May 2019) - Gardner, Benjamin; Matousek, Pavel; Stone, Nick
Abstract : Here we demonstrate light mediated heating of nanoparticles confined deep inside mammalian tissue, whilst directly monitoring their temperature non-invasively using a form of deep Raman spectroscopy, T-SESORS. Abstract : Here we demonstrate light mediated heating of nanoparticles confined deep inside mammalian tissue, whilst directly monitoring their temperature non-invasively using a form of deep Raman spectroscopy, T-SESORS. One of the main barriers to the introduction of photo-thermal therapies (PTT) has been recognised as the inability to directly monitor the local temperature deep within the tissue at the point of therapy. Here Au nanoparticles with a Raman reporter molecule (temperature reporters) are used in combination with Au nanoshells (heat mediators) to provide simultaneously heating under NIR illumination and direct spectroscopic monitoring of local temperature deep within mammalian tissues. The surface enhanced Raman signal was read out at the tissue surface using a transmission geometry in this example and the temperature of the tissue was ascertained from the anti-Stokes to Stokes Raman reporter. This approach opens the prospect of non-invasive hyperthermia treatments with direct temperature feedback from deep inside within tissue, where nanoparticles can be used to both provide localised heating and accurately monitor the local temperature.